Assessing the Potential for Directing Electrification Towards Productive Use in Rural Mozambique - Jakobsson, Niklas; Karheiding, Carl (My University, 2012)
It is generally accepted that electricity brings a number of social benefits such as better healthcare, better education, increased security due to street lightning and lower household expenditure due to a cheaper light source. Electricity is also expected to bring economic benefits in the form of income-generating opportunities, this happens less regularly and it cannot be expected that production springs from the ground once electricity arrives to a region; a larger understanding of the connection between electrification and its effect on production is therefore needed. Our Master of Science thesis describes the methodology behind, and the results of, an 8 week field survey on the connection between rural electrification and productive use carried out in the province of Cabo Delgado in northern Mozambique. The idea is to investigate if existing production can be utilized as an anchor for electrification in the sense that it can either provide a strong consumption basis to increase the economic viability for grid extension, or if it can be utilized for larger income-generation when electrified. The project springs from an idea in the scientific literature to identify productive activities in rural settings and utilize them as anchors in the described sense. Specifically an electrification project in Ribaue district in northern Mozambique is frequently cited as a success story when utilizing productive use in electrification processes. The results show that there are not enough, or large enough, production units on the countryside in northern Mozambique for any of them to be utilized as an anchor in the hoped sense and thereby that the example from Ribaue is not reproducible generally. The only wide-spread type of production is milling, this activity is too small to generate any substantial incomes from the electric utility and its income-generating effect for a village is, compared to the number of inhabitants, limited; larger activities are limited to one cotton factory, two cashew nut processing factories, a couple of saw mills and a couple of salt production sites (excluding tourism). The cotton factory is the single most substantial electricity anchor, both from supplier perspective and due to its income generating effect on the local people. Finally, to effectively utilize productive use for income generation, we give the recommendation for a multi-cooperative effort between the government, foreign aid institutions and NGOS to spur simultaneous creation of infrastructural, complementary service and additional business project expansion. In the light of this recommendation, the emphasis on existing production represents a shortcut that we do not feel is possible to take in northern Mozambique.
Keywords: Energi; Miljöteknik; Hållbar utveckling; Building Futures; Energy; Environmental engineering; Sustainable Development; Building Futures